2016
DOI: 10.3168/jds.2016-10990
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor α promotes the synthesis of monounsaturated fatty acids in goat mammary epithelial cells via the control of stearoyl-coenzyme A desaturase 1 in an SREBP-1-dependent manner

Abstract: Stearoyl-coenzyme A desaturase 1 (SCD1) is a pivotal enzyme in the biosynthesis of monounsaturated fatty acids (MUFA). It is tightly regulated by transcription factors that control lipogenesis. In nonruminants, liver X receptor α (LXRα) is a nuclear receptor and transcription factor that acts as a key sensor of cholesterol and lipid homeostasis. However, the mechanism whereby LXRα regulates the expression and transcriptional activity of SCD1 in ruminant mammary cells remains unknown. In this study with goat ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Similar to the above findings, the activation of LXR directly increased the expression of lipogenic genes in bovine mammary epithelial cells in an SREBP1-independent fashion (Oppi-Williams et al, 2013). Several studies demonstrated a direct effect of LXR on the expression of SREBF1 and the downstream genes FASN and SCD1 in goat mammary cells (Li et al, 2015b;Yao et al, 2016). More recent is the demonstration that the LXRβ also control the expression of SREBP1c and FASN in goat mammary cells (Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar to the above findings, the activation of LXR directly increased the expression of lipogenic genes in bovine mammary epithelial cells in an SREBP1-independent fashion (Oppi-Williams et al, 2013). Several studies demonstrated a direct effect of LXR on the expression of SREBF1 and the downstream genes FASN and SCD1 in goat mammary cells (Li et al, 2015b;Yao et al, 2016). More recent is the demonstration that the LXRβ also control the expression of SREBP1c and FASN in goat mammary cells (Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…The role of LXR in controlling milk fat synthesis was initially demonstrated by work conducted in bovine mammary cells in vitro, where activation of LXRα by the specific agonist T0901317 increased the expression of SREBP1 and augmented de novo fatty acid synthesis (McFadden and Corl, 2010). Since then, much work has been done to clarify the transcriptional regulation mechanism of LXR on SREBP1 and the consequence on milk fat synthesis in ruminants (Wang et al, 2012;Oppi-Williams et al, 2013;Li et al, 2015b;Yao et al, 2016;Shi et al, 2017). However, much work remains to be done to determine whether the activation of LXR affects the network of genes involved in milk fat synthesis (Bionaz and Loor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes mellitus type I Sprague-Dawley rats models [29], serum TC and both serum and hepatic TG were decreased by TB. In the meanwhile, this effect accompanied by suppression of oxidative stress, as well as liver X receptor-α and Sterol regulatory element binding protein-1 which involved in regulating lipid synthesis and metabolism [30]. Secondly, insulin resistance could in uence their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Sterol regulatory element binding transcription factor 1 (Srebp1) and liver X receptor α (Lxrα) play central roles in the transcriptional regulation of lipogenesis . In mammals, Srebp1 transactivates the scd1 promoter through sterol response elements (SREs) and nuclear factor (NF‐Y) binding sites . Lxrα indirectly promotes scd1 expression by increasing Srebp1 abundance .…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, Srebp1 transactivates the scd1 promoter through sterol response elements (SREs) and nuclear factor (NF‐Y) binding sites . Lxrα indirectly promotes scd1 expression by increasing Srebp1 abundance . In addition to Srebp1 and Lxrα, the peroxisome proliferator–activated receptor γ (Pparγ) is also required for lipid synthesis .…”
Section: Introductionmentioning
confidence: 99%